Upaya Guru Bimbingan dan Konseling dalam Menumbuhkan Minat Belajar Siswa Pasca Pandemi Covid-19 di MAN 1 Agam - Oga Sandria; Syawaluddin Syawaluddin; Sri Hartati; Hidayani Syam (Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This research is motivated by the existence of problems that occur at MAN 1 Agam, namely learning interest is one of the factors that is very important for the success of learning that students have, interest arises from within the students themselves. Factors from outside the interest in learning are how the teacher teaches. The role of the teacher is very important to foster student interest in learning, one of which is by teaching in a fun way, providing constructive motivation. The purpose of this study is to determine the efforts of Guidance and Counseling teachers in fostering students' interest in learning after the Covid-19 pandemic. This research is a type of field research with a qualitative approach. Informants. The key informant in this study is the Guidance and Counseling teacher, while the supporting informants are five students who are foster children of the Guidance and Counseling teacher, The data collection technique that researchers use is interviews. Data analysis carried out in this study through steps, namely data reduction, data presentation and drawing conclusions. Data triangulation is used as a data validity check. The results showed that students' desire to learn during the pandemic was higher than students during the non-pandemic period. This can be seen from students' desire to learn more, their willingness to learn more actively, and their enthusiasm for learning offline. Even so, there are still a few students who have a strong desire to learn. Giving attention to teachers in order to develop students' critical thinking skills is very important for students who lack strong critical thinking skills. Therefore, counseling teachers are very effective in helping students increase their desire to learn. As for the BK teacher, efforts: taking a personal approach such as providing support, conducting counseling, giving praise and recognition.